Anabolic Steroids Use Is Associated with Impairments in Atrial and Ventricular Cardiac Structure and Performance in Athletes - Grandperrin, Antoine; Schuster, Iris; Moronval, Pierre; Izem, Omar; Rupp, Thomas; Obert, Philippe; Nottin, Stéphane (Medicine and science in sports and exercise, 2022)
Despite potential severe cardiac side effects, anabolic androgenic steroids (AAS) are increasingly used by strength athletes. However, previous echocardiographic studies focused on the left ventricular (LV) strains but did not assess LV twist and untwist mechanics. Moreover, left atrial (LA) function has been often neglected, and its stiffness, an important determinant of LA reservoir function, has never been challenged. The aim of this study was to investigate the effects of AAS on LA and LV morphologies and functions in strength athletes. Fifty subjects including 20 strength-trained young athletes age 32.0 ± 8.5 yr with a mean duration of AAS use of 4.7 ± 1.8 yr (users), 15 athletes with no history of AAS use (nonusers) and 15 sedentary controls underwent speckle tracking echocardiography to assess LA and LV morphology and function. Users showed higher LA reservoir dysfunction than nonusers (33.7% ± 10.9% vs 44.9% ± 9.9% respectively, P = 0.004) and higher LA stiffness (0.13 ± 0.05 vs 0.19 ± 0.08 A.U., respectively; P = 0.02), higher LV mass index and lower global and regional LV diastolic and systolic dysfunction (global longitudinal strain: -15.5% ± 3.2% vs -18.9% ± 1.8% respectively; P = 0.003), with a drop of LV twist-untwist mechanics (untwisting velocity: 61.5°·s-1 ± 20.2°·s-1 vs 73.7°·s-1 ± 16.1°·s-1 respectively, P = 0.04). There were significant correlations between LV mass and LV apical rotation (P = 0.003, r = 0.44) and diastolic longitudinal strain rate (P = 0.015, r = 0.33). Our results showing significant LA and LV remodeling and dysfunctions in young AAS using athletes are alarming. Screening echocardiography based on speckle tracking echocardiography parameters for early diagnosis, as well as a stronger awareness in athletes and in physicians are warranted in this context.